Rethinking Patterns Development of Aceh's Socio-Economic Welfare After Two Decades of Implementing Asymmetric Autonomy "Special Autonomy" - Hendy Setiawan (Journal of Government and Political Issues, 2022)
This study aims to determine the two decades of special autonomy in Aceh with the existence of special autonomy funds, but it does not have an impact on economic and social welfare in Aceh. Poverty and economic inequality are still rife, even though special autonomy is to provide space for the implementation of regional innovation and creativity in government administration. Several factors cause Aceh's special autonomy funds not to work correctly or still cause poverty in the Aceh region, namely development policies, the corruption that is still rampant, and poor management of the special autonomy funds. The development policy factor is related to the government, which favors industry players. Then, corruption is rampant because the Aceh government uses the special autonomy funds for its interests. The poor management of special autonomy funds is related to delays and errors in program planning from the provincial to regional levels. Then, the method in this study with a qualitative approach. Furthermore, the theoretical approach in this research is welfare theory to combine special autonomy as a way out of the slump in Aceh to date. This study shows that the Aceh Government is still misusing the Aceh Special Autonomy Fund because it is proven not to be prosperous, and the Acehnese people still experience the highest poverty rate in Sumatra. This research is essential because it needs to know and provide information to readers about how Aceh’s special autonomy funds are not being used appropriately, and the Aceh government still commits much corruption.